POST-BUCKLING ANALYSIS OF FUNCTIONALLY GRADED THREE-DIMENSIONAL BEAMS UNDER THE INFLUENCE OF TEMPERATURE - Akbas, Seref Doguscan; Kocaturk, Turgut (TAYLOR & FRANCIS INC, 2013)
In this study, post-buckling behavior of functionally graded beams under the influence of temperature loading is investigated by using total Lagrangian finite element model of three-dimensional continuum approximations. Material properties of the beam are both temperature-dependent and position-dependent. In this study, there is no restriction on the magnitudes of deflections and rotations in the beam. The considered highly non-linear problem is solved by using incremental displacement-based finite element method in connection with Newton-Raphson iteration method. With the effects of material gradient property and thermal load, thermal post-buckling configurations are illustrated in detail in post-buckling cases.
Keywords: Functionally graded materials; Thermal post-buckling analysis; Three-dimensional solid continuums; Total lagrangian finite element model; TIMOSHENKO BEAMS; FREE-VIBRATION; SANDWICH BEAM; STRESSES; Thermodynamics; Mechanics